Force Majeure as a Reason for Release from Debtor's Obligations (Analysis of Settlement of Bank Credit Agreements Delinquent Due to the Earthquake in Yogyakarta) - Hanim, Lathifah; Prasetia Wiranto, Agus (Jurnal Hukum Khaira Ummah, 2026)
This study aims to analyze bank efforts in resolving credit agreements that are in default due to force majeure due to the earthquake in Yogyakarta, examine the principles used in the settlement practices, and formulate the principles that should be prioritized in conditions of fundamental changes in circumstances. The study uses a combined legal method, namely a doctrinal and non-doctrinal approach with a qualitative nature. Data were obtained from primary, secondary, and tertiary legal materials, and strengthened by in-depth interviews and Focus Group Discussions, then analyzed normatively and interactively. The results of the study indicate that the settlement of non-performing loans after the earthquake is no longer solely based on the credit agreement clauses made by the parties, but also on Bank Indonesia's special post-disaster policies. The forms of settlement taken include rescheduling, reconditioning, restructuring, collateral seizure, and execution. This study also found that in practice, settlement is more appropriate through renegotiation between creditors and debtors based on the principle of rebus sic stantibus, rather than solely the principle of pacta sunt servanda. Thus, the principle of rebus sic stantibus is more relevant for use in resolving bad debts due to earthquakes, because it is able to accommodate fundamental changes in circumstances while still paying attention to good faith, proportionality, and justice for the parties.